Innovation Communication of Compass Shoes to Attract Young People in Bogor City - Jajat Sudrajat (Riviera Publishing, 2026)
This research explains how Compass, a well-known local shoe brand from Indonesia, communicates its product innovation to attract young consumers in Bogor City. The principal conception of the study is that communication plays an extremely significant part in familiarizing the audience with innovation and helping them value it, particularly within the footwear sector, which continues to expand and compete in both local and global markets. The purpose of this study is to describe and analyze how Compass develops and delivers messages about its innovative products to young people who are considered to be active, creative, and open to new ideas. This study employs a qualitative descriptive approach, where data were gathered through interviews, observation, and documentation. The findings show that Compass applies creative and consistent communication by combining local identity, digital media, and storytelling to build a strong emotional connection with young consumers. The study also finds that innovation at Compass is not only about product design but also about how the brand positions itself as part of youth culture and local pride. In general, this study infers that appropriately presented innovation communication can enhance the reputation of local brands and earn dedicated consumers with the help of emotional appeal, authenticity, and substantive interaction